2003
DOI: 10.1016/s1535-6108(03)00054-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic amplification and oncogenic properties of the KCNK9 potassium channel gene

Abstract: Representational difference analysis (RDA) of human breast cancer was used to discover a novel amplicon located at chromosomal region 8q24.3. We examined a series of breast cancer samples harboring amplification of this region and determined that KCNK9 is the sole overexpressed gene within the amplification epicenter. KCNK9 encodes a potassium channel that is amplified from 3-fold to 10-fold in 10% of breast tumors and overexpressed from 5-fold to over 100-fold in 44% of breast tumors. Overexpression of KCNK9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
213
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(231 citation statements)
references
References 23 publications
7
213
0
5
Order By: Relevance
“…Several KCNK channel genes, for example, KCNK9 [43], are overexpressed in breast and lung cancers, and the gene KCNK2 can promote prostate cancer cell's growth [40,44]. …”
Section: Resultsmentioning
confidence: 99%
“…Several KCNK channel genes, for example, KCNK9 [43], are overexpressed in breast and lung cancers, and the gene KCNK2 can promote prostate cancer cell's growth [40,44]. …”
Section: Resultsmentioning
confidence: 99%
“…These biophysical properties are not simply markers but are functional signals; misexpression of an ion transporter induces tumorigenicity in fibroblasts (50), and inhibition of EAG channel function suppresses neoplasm in an animal model in vivo (51). Ion channel function controls the proliferation rate and invasiveness of a number of cell types that often form tumors (49,(52)(53)(54)(55), and overexpression of KCNK9 (strongly overexpressed in breast cancer) promotes tumor formation and confers resistance to hypoxia and serum deprivation (56). Misexpression of KCNE1 did not induce tumors per se.…”
Section: Discussionmentioning
confidence: 99%
“…The coding region of TASK3 was cloned at BamHI and EcoRI sites of the pLPC retroviral expression vector (15) to generate pLPC-TASK3. Site-directed mutagenesis was performed to change Gly-95 to Glu to create pLPC-TASK3 G95E , by using QuickChange site-directed mutagenesis kit (Stratagene) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The physiological functions of TASK channels are largely unknown, though their roles in the regulation of breathing (12,13), aldosterone secretion (5) and anesthetic-mediated neuronal activity (14) have been proposed. Recently, we showed that TASK3 is amplified in 10% of breast cancers and is overexpressed at a higher frequency of breast, lung, colon, and metastatic prostate cancers (15), suggesting that TASK3 may play a role in pathogenesis of some human carcinomas.…”
mentioning
confidence: 99%